Exploring the association between serum vitamins and CAP-defined hepatic steatosis in lean and non-lean adults with NAFLD: A cross-sectional study - Caijuan Hong; Lili Jiang; Lulu Xia (PLoS ONE, 2026)
Background Non-alcoholic fatty liver disease (NAFLD) is highly prevalent worldwide, yet the role of serum vitamins in hepatic fat accumulation, particularly across lean and non-lean individuals, remains incompletely understood. This study evaluated associations between serum levels of vitamins A, C, D, and E and the degree of CAP-defined hepatic steatosis in lean and non-lean adults. Methods Data from the 2017–2018 NHANES were analyzed. Weighted multivariable linear regression was performed in lean and non-lean adults to assess the associations between serum vitamin levels and CAP-defined hepatic steatosis, using unadjusted, demographic-adjusted, and fully adjusted models. Results No significant linear associations were observed between serum vitamin levels and the degree of hepatic steatosis in lean adults. A nonlinear association with serum vitamin C was observed, indicating a threshold effect. The association between vitamin C and the degree of liver fat accumulation also varied by diabetes status. In non-lean adults, serum vitamin C consistently showed an inverse association with CAP-defined hepatic steatosis (Model 2: β = −0.16, 95% CI: −0.25 to −0.07), as did vitamins A (β = −6.34, 95% CI: −10.43 to −2.25) and D (β = −0.13, 95% CI: −0.21 to −0.04). Conclusion Higher serum levels of vitamins A, C, and D were associated with lower CAP-defined hepatic steatosis in non-lean adults, while a nonlinear relationship involving vitamin C was observed in lean individuals. Further studies are needed to confirm these findings.